2017
DOI: 10.1051/sicotj/2016042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of academic collaboration and quality of clinical orthopaedic research conducted in low- and middle-income countries

Abstract: Background: Little is known about the quality of orthopaedic investigations conducted in low- and middle-income countries (LMICs). Academic collaboration is one model to build research capacity and improve research quality. Our study aimed to determine (1) the quality of clinical orthopaedic research conducted in LMICs, (2) the World Bank Regions and LMICs that publish the highest quality studies, (3) the pattern of collaboration among investigators and (4) whether academic collaboration between LMIC and non-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Only 10% of the 132 publications from LICs were classified as level I or II evidence, with the majority of articles being case series or level IV evidence. Our findings mirror that of a recent study reported by Wu et al [18], who found that only 10% of the studies from LMICs evaluated reported level I or II evidence but that when investigators in LMICs and from HICs collaborated, research was of a higher evidence quality [18]. The present study similarly found that of the nine articles that were classed as high-level evidence, 78% ( n = 7) were collaborative articles.…”
Section: Discussionsupporting
confidence: 89%
“…Only 10% of the 132 publications from LICs were classified as level I or II evidence, with the majority of articles being case series or level IV evidence. Our findings mirror that of a recent study reported by Wu et al [18], who found that only 10% of the studies from LMICs evaluated reported level I or II evidence but that when investigators in LMICs and from HICs collaborated, research was of a higher evidence quality [18]. The present study similarly found that of the nine articles that were classed as high-level evidence, 78% ( n = 7) were collaborative articles.…”
Section: Discussionsupporting
confidence: 89%
“…Limited evidence is available on the perception of the importance of research quality in capacity building studies from the MENA region. Approaches to increase research quality in other fields such as orthopaedic research in LMICs identified academic collaboration, defined as the inclusion of LMIC and non-LMIC investigator, to be associated with higher levels of evidence and thus higher quality studies [ 28 ]. In cancer treatment trials, international and national academic collaboration is supported by a way to improve cancer therapy and patient outcomes [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only are locally relevant questions answered but a culture of research and critical assessment of outcomes is also fostered in an environment that trains future leaders. Our prior work has demonstrated the positive effects of collaboration on the quality of clinical research generated in LMICs ( 28 ).…”
Section: Methodological Aspectsmentioning
confidence: 99%